Bacteriophage typing of Shigella sonnei. - Pruneda, R C (1977)
A bacteriophage-typing schema was developed for differentiating strains of Shigella sonnei. Sixty-seven bacteriophages were obtained from other collections, and 36 bacteriophages were isolated from sewage. From these 103 bacteriophages, a provisional set of 12 was chosen by computer analysis as being the most sensitive in differentiating strains of S. sonnei isolated in the United States. The provisional schema was used to type 265 strains from different geographical areas. It divided them into 87 different lysis patterns, and all 265 strains were typable. Smooth and rough colonial variants of the same strain had different lysis patterns, so the technique was standardized to type rough colonies only. Reproducibility was difficult to obtain until all conditions were carefully standardized. Changes in results were noted even on different lot numbers of Trypticase soy agar, which was defined as the standard medium. So that the medium would not be a variable, 100 pounds (ca 453.5 kg) of the same lot number was purchased. Bacteriophage typing was very useful in differentiating strains, and work should continue on establishing a standarized schema.